2015
DOI: 10.1002/erv.2382
|View full text |Cite
|
Sign up to set email alerts
|

Approach Bias Modification in Food Craving—A Proof‐of‐Concept Study

Abstract: The aim of the present proof-of-concept study was to test a novel cognitive bias modification (CBM) programme in an analogue sample of people with subclinical bulimic eating disorder (ED) psychopathology. Thirty participants with high levels of trait food craving were trained to make avoidance movements in response to visual food stimuli in an implicit learning paradigm. The intervention comprised ten 15-minute sessions over a 5-week course. At baseline, participants showed approach and attentional biases towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 47 publications
5
66
1
1
Order By: Relevance
“…Since there were only seven comparisons in the PP‐design category and these were of different interventions, no meta‐analysis was calculated. A proof‐of‐concept study in bulimic participants showed large pre‐post effects of a 10‐session AAT on subjective craving . Two studies investigating cue exposure in virtual reality showed medium to huge pre‐post ES on craving .…”
Section: Resultsmentioning
confidence: 99%
“…Since there were only seven comparisons in the PP‐design category and these were of different interventions, no meta‐analysis was calculated. A proof‐of‐concept study in bulimic participants showed large pre‐post effects of a 10‐session AAT on subjective craving . Two studies investigating cue exposure in virtual reality showed medium to huge pre‐post ES on craving .…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings have also been found with respect to reactive inhibition, although the findings have been less consistent than data on reward-related inhibition (for review, see Bartholdy et al, 2016). As a result, behavioral paradigms are emerging that seek to increase inhibitory control to improve eating behavior (Lawrence et al, 2015; for reviews, see Brockmeyer et al, 2015; Bartholdy et al, 2016; Turton et al, 2016), which may be useful both in the treatment of eating disorders/obesity, but also as possible preventative measures for individuals in the community. However, the relationships between hunger and the different elements of inhibitory control are not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…In our own proof‐of‐principle study, ABM was associated with significant reductions in ED symptoms, trait food craving and cue‐elicited food craving as well as in (the targeted) approach bias towards food in individuals with high levels of trait food craving and sub‐threshold ED symptoms (Brockmeyer et al, ). In the present study, participants in both groups experienced significant and large reductions in binge eating, ED symptoms, trait food craving, and food cue reactivity.…”
Section: Discussionmentioning
confidence: 90%